Ionic‐liquid‐based dispersive liquid–liquid microextraction combined with magnetic solid‐phase extraction for the determination of aflatoxins B1, B2, G1, and G2 in animal feeds by high‐performance liquid chromatography with fluorescence detection. Issue 19 (7th September 2016) - Zhao, Jiao; Zhu, Yan; Jiao, Yang; Ning, Jinyan; Yang, Yaling
Abstract : A novel two‐step extraction technique combining ionic‐liquid‐based dispersive liquid–liquid microextraction with magnetic solid‐phase extraction was developed for the preconcentration and separation of aflatoxins in animal feedstuffs before high‐performance liquid chromatography coupled with fluorescence detection. In this work, ionic liquid 1‐octyl‐3‐methylimidazolium hexafluorophosphate was used as the extractant in dispersive liquid–liquid microextraction, and hydrophobic pelargonic acid modified Fe3 O4 magnetic nanoparticles as an efficient adsorbent were applied to retrieve the aflatoxins‐containing ionic liquid. Notably, the target of magnetic nanoparticles was the ionic liquid rather than the aflatoxins. Because of the rapid mass transfer associated with the dispersive liquid–liquid microextraction and magnetic solid phase steps, fast extraction could be achieved. The main parameters affecting the extraction recoveries of aflatoxins were investigated and optimized. Under the optimum conditions, vortexing at 2500 rpm for 1 min in the dispersive liquid–liquid microextraction and magnetic solid‐phase extraction and then desorption by sonication for 2 min with acetonitrile as eluent. The recoveries were 90.3–103.7% with relative standard deviations of 3.2–6.4%. Good linearity was observed with correlation coefficients ranged from 0.9986 to 0.9995. The detection limits were 0.632, 0.087, 0.422 and 0.146 ng/mL for aflatoxins B1, B2, G1, and G2, respectively. The results were also compared with the pretreatment method carried out by conventional immunoaffinity columns.